2012
DOI: 10.1021/la301608k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Poly(dimethylsiloxane)-block-poly(2-methyloxazoline) Polymersomes Probed by Atomic Force Microscopy

Abstract: Poly(dimethylsiloxane)-block-poly(2-methyloxazoline) (PDMS-b-PMOXA) vesicles were characterized by a combination of dynamic light scattering (DLS), cryogenic transmission electron microscopy (cryo-TEM), and atomic force microscopy imaging and force spectroscopy (AFM). From DLS data, a hydrodynamic radius of ~150 nm was determined, and cryo-TEM micrographs revealed a bilayer thickness of ~16 nm. In AFM experiments on a silicon wafer substrate, adsorption led to a stable spherical caplike conformation of the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 44 publications
7
78
0
1
Order By: Relevance
“…This is in agreement with a previous report where the flattening effect of surface activeness on (PDMS-b-PMOXA) vesicles adsorbed on oxidized Si wafers and mica substrates was explored. 21 This behavior was also supported by another study which showed that the increasing molecular recognition between streptavidin layers and biotinylated liposomes induced a height decrease in the vesicle structures. 49 Furthermore, particle size distributions of the surfaceimmobilized polymersomes were compared with the data obtained from cryo-TEM analysis ( Figure 5, Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This is in agreement with a previous report where the flattening effect of surface activeness on (PDMS-b-PMOXA) vesicles adsorbed on oxidized Si wafers and mica substrates was explored. 21 This behavior was also supported by another study which showed that the increasing molecular recognition between streptavidin layers and biotinylated liposomes induced a height decrease in the vesicle structures. 49 Furthermore, particle size distributions of the surfaceimmobilized polymersomes were compared with the data obtained from cryo-TEM analysis ( Figure 5, Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 55%
“…Similar approaches have been applied previously for liposomes, 33 polyelectrolyte multilayer capsules, 34 natural membrane nanovesicles, 35 and different polymersome structures. 21,22 Hence, as illustrated in Scheme 1, we first performed the surface immobilization of multifunctional and photo-crosslinked polymersomes by strong adamantane−β-cyclodextrin host−guest interactions. Before proceeding to responsive behavior analysis, the level of binding forces between β-cyclodextrin coated substrates and adamantane decorated polymersomes was studied to gain information about the shape deformation of the vesicles when adhering to the surfaces.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This finding indicates that our nanoparticles are mechanically stable enough to be shape‐persistent during adsorption and also drying, where strong capillary forces will occur. In comparison, for poly(dimethylsiloxane)‐ b ‐poly(2‐methyloxazoline), which is known to form spherical vesicles in solutions, a height‐to‐width ratio of 1:6.25 has been reported upon adsorption to a solid substrate …”
Section: Resultsmentioning
confidence: 99%
“…69,70 A microscopia de fluorescência também necessita de marcador fluorescente nas vesículas e permite estudar processos dinâmicos como difusão. 66 A microscopia de força atômica (MFA) pode ser usada para avaliar características mecânicas da bicamada dos PL 71 como fizeram Chen e coloaboradores que, por meio de MFA, avaliaram a rigidez de membranas de poliestireno-b-poli(ácido)acrílico. 72 Assim como para outros NC, a taxa de encapsulação pode ser calculada diretamente nos sistemas após tratamentos que desagregam os PL ou indiretamente no sobrenadante após centrifugação dessas nanoestruturas.…”
Section: Principais Técnicas De Caracterizaçãounclassified